2014
DOI: 10.1103/physrevb.89.224416
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic excitations and anomalous spin-wave broadening in multiferroic FeV2O4

Abstract: We report on the different roles of two orbital-active Fe2+ at the A site and V3+ at the B site in the magnetic excitations and on the anomalous spin-wave broadening in FeV2O4. FeV2O4 exhibits three structural transitions and successive paramagnetic (PM)-collinear ferrimagnetic (CFI)-noncollinear ferrimagnetic (NCFI)/ferroelectric transitions. The high-temperature tetragonal/PM-orthorhombic/CFI transition is accompanied by the appearance of a large energy gap in the magnetic excitations due to strong spin-orbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…In contrast, the peak splitting at other temperatures is similar to that in past studies [12]. In the NPD study, signs of these transitions were also observed, consistent with recent literature [13,20,21]. However, the peak splitting was not observed as clearly as in the SPD study because of the lower angular resolution of NPD.…”
Section: Synchrotron and Neutron Diffraction Measurementscontrasting
confidence: 52%
See 1 more Smart Citation
“…In contrast, the peak splitting at other temperatures is similar to that in past studies [12]. In the NPD study, signs of these transitions were also observed, consistent with recent literature [13,20,21]. However, the peak splitting was not observed as clearly as in the SPD study because of the lower angular resolution of NPD.…”
Section: Synchrotron and Neutron Diffraction Measurementscontrasting
confidence: 52%
“…However, the OO models of V 3+ ions at T N2 , suggested by Nii et al [11] and Kang et al [18], are contradictory. Additionally, the origins and structural properties of the low-temperature phase including the elongated tetragonal phases [12] are still disputed despite numerous experimental and theoretical efforts [11][12][13][14][15][16][17][18][19][20][21]. In this paper, we tackle the accurate structure analysis with high-resolution synchrotron diffraction and neutron diffraction by using polycrystalline samples as well as single crystals of FeV 2 O 4 and orbitally diluted materials for each A and B site.…”
Section: Introductionmentioning
confidence: 99%
“…[9] For the particular case of FeV2O4 (stoichiometric FVO), it possesses unique properties on account of the interaction of the two cations through their oxygen octahedral network (Fe 2+ and V 3+ on the tetrahedral and octahedral sites, respectively) that controls this interplay among spin, orbital, and lattice degrees of freedom. [2][3]10] For instance, the magnetoelectric and ferroelectric properties of polycrystalline FeV2O4 (and related chemical formulations) have been reported. Takei et al [11] found that the capacitance of polycrystalline FeV2O4 exhibits a magnetic This article is protected by copyright.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, despite the lack of charge degrees of freedom due to the Mott insulator, both electronic correlations and geometric frustration are present, resulting in an interplay between the different degrees of freedom, such as spin, orbital, and lattice, which leads to three successive phase transitions with decreasing temperature. [15][16][17][18][19][20][21][22][23][24] FeV 2 O 4 has been widely studied from both experimental and theoretical perspectives; however, owing to the intertwining of the multiple degrees of freedom, it is difficult to understand the orbital state completely. AV 2 O 4 with other cations at the Fe site has been studied to avoid multiple degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%